Prosopis juliflora (Swartz) DC.: an invasive alien in community grazing lands and its control through utilization in the Indian Thar Desert. Issue 4 (2nd October 2019) - Pandey, C. B.; Singh, A. K.; Saha, D.; Mathur, B. K.; Tewari, J. C.; Kumar, M.; Goyal, R. K.; Mathur, M.; Gaur, M. K.
Abstract: Prosopis juliflora (Swartz) DC., an invasive alien plant species, is known as a threat to biodiversity and ecosystem services world over. It has heavily invaded community grazing lands (CGLs) in the Indian Thar Desert. The present study reports effects of four canopy sizes, (i.e. small, medium, large and no-canopy/open plot), of P. julflora shrub on native vegetation and soil fertility (0–20 cm depth) in the CGLs distributed in Jodhpur, Pali, and Sirohi districts in the Desert. In addition, economic profitability of P. juliflora based three enterprises, (i.e. charcoal making, pod-flour making, and sheep rearing in the grasslands if developed in the CGLs), was evaluated to find out invasion control measures of the shrub through utilization. Soil organic carbon (SOC), total N, available P and K, and mineral N (NO3 − –N, NH4 + –N) and soil-moisture contents were higher under the shrub canopy than in open plot; and they were the highest under the large and lowest under the small canopy sizes. But, light intensity (Lux) declined under the canopy. The decline, however, was the highest under the large and lowest under the small canopy sizes. Composition of native plant species changed and their richness and diversity declined under the canopy, but was higher under the larger canopy size. Economic analyses revealed that investment was the highest (5476US$ ha −1 ) in the charcoal and lowest (486US$ ha −1 ) in pod-flour enterprise, but gross profit and net present value (NPV) were the highest (10740US$ ha −1 and 5264US$ ha −1, respectively) in the charcoal and lowest (895US$ ha −1 and 409US$ ha −1, respectively) in pod-flour enterprise. Other economic parameters, like the annuity and internal rate of return (IRR), were also the highest in the charcoal and lowest in pod-flour enterprise suggesting that the charcoal enterprise is economically the most profitable enterprise; and it may control the invasion of the P. juliflora in the Desert.